1990
DOI: 10.1093/bja/65.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effect of Metoclopramide on Cholinesterases and Suxamethonium Metabolism

Abstract: In obstetric patients undergoing postpartum tubal ligation, we found that metoclopramide produced dose-dependent prolongation of suxamethonium-induced neuromuscular block. Mean block times after suxamethonium 1 mg kg-1 were 8.0 min, 9.83 min and 12.45 min for control and metoclopramide 10 mg and metoclopramide 20 mg groups, respectively. A laboratory study was therefore conducted on the inhibition of human plasma cholinesterase (PCHE) and erythrocyte acetylcholinesterase (ACHE) activity by varying concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…This range spans most of the dose response curve for inhibition by metoclopramide. This supports previous observations [5] that metoclopramide can produce a significant prolongation of the action of drugs metabolized by this enzyme. This problem will be most marked in circumstances where the level of enzyme activity is reduced initially [10] such as term pregnancy [11] (Kao [5] showed that in the immidiate post-partum period administration of metoclopramide 20 mg prolongs the duration of action of suxamethonium from 8.0 to 12.5 rain), or where particularly high doses of metoclopramide are used, as in antiemetic therapy for cancer chemotherapy (Graham, Burgess and MacMillan, unpublished data).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This range spans most of the dose response curve for inhibition by metoclopramide. This supports previous observations [5] that metoclopramide can produce a significant prolongation of the action of drugs metabolized by this enzyme. This problem will be most marked in circumstances where the level of enzyme activity is reduced initially [10] such as term pregnancy [11] (Kao [5] showed that in the immidiate post-partum period administration of metoclopramide 20 mg prolongs the duration of action of suxamethonium from 8.0 to 12.5 rain), or where particularly high doses of metoclopramide are used, as in antiemetic therapy for cancer chemotherapy (Graham, Burgess and MacMillan, unpublished data).…”
Section: Discussionsupporting
confidence: 92%
“…These studies have been conducted using high dilutions of the enzyme source. The enzyme concentrations in vivo are 30-300 times greater than in the cuvette [4][5] competitive, the effective free inhibitor concentrations may be far lower at enzyme concentrations approaching those in vivo. On this basis the previous authors' assumptions that cuvette-derived data would directly reflect in vivo conditions has been questioned [6].…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…They were selected, as was their final concentration in the assay, based on the literature: edetic acid (EDTA) and chloromercuribenzoate (1 mM and 100 M, respectively; in-hibitors of A-esterases), paraoxon, physostigmine, metoclopramide, sodium fluoride (NaF), and bis-pnitrophenyl phosphate (BNPP) (all at 100 M; inhibitors of B-esterases), acetazolamide (100 M, inhibitor of carboxylanhydrase), and acetylsalicylic acid (100 M; aspecific inhibitor of esterases) (18)(19)(20)(21)(22)(23). Incubation mixtures contained whole blood (980 l), 700 M LEV (added as 10 l in water), and the inhibitor (added as 10 l in either water or methanol).…”
Section: In Vitro Assay For Levetiracetam Hydrolysis By Using Human Lmentioning
confidence: 99%